2008
DOI: 10.1152/ajpheart.01371.2007
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia modulates nitric oxide-dependent vasodilation and capillary perfusion during ischemia-reperfusion-induced damage

Abstract: Bertuglia S. Intermittent hypoxia modulates nitric oxide-dependent vasodilation and capillary perfusion during ischemia-reperfusion-induced damage. Am J Physiol Heart Circ Physiol 294: H1914-H1922, 2008. First published February 22, 2008 doi:10.1152/ajpheart.01371.2007.-The microvascular function of nitric oxide (NO) during ischemia-reperfusion (I/R) in intermittent hypoxia (IH)-pretreated hamsters was analyzed using 20 mg/kg of the nonselective NO inhibitor N -nitro-Larginine methyl ester (L-NAME) and 5 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
4
21
0
Order By: Relevance
“…] period, proposing a cardioprotective role for NOSderived NO against the oxidative episodes occurring during H/R. In agreement with our results, other authors working in another organ and species reported that L-NAME increased the concentrations of TBARS after intermittent hypoxia in hamster-cheek-pouch microcirculation (Bertuglia et al, 2008). Actually, several mechanisms may explain the protective effects of NO against oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…] period, proposing a cardioprotective role for NOSderived NO against the oxidative episodes occurring during H/R. In agreement with our results, other authors working in another organ and species reported that L-NAME increased the concentrations of TBARS after intermittent hypoxia in hamster-cheek-pouch microcirculation (Bertuglia et al, 2008). Actually, several mechanisms may explain the protective effects of NO against oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…2). Because it is well known that L-NAME is a NOS inhibitor (Bertuglia et al, 2008;Viñ as et al, 2006), the decrease reported here in both NOx levels and in situ NOS activity should be attributed to NOS inhibition.…”
Section: Discussionmentioning
confidence: 58%
“…Animal studies (2, 6) have indicated that acute intermittent hypoxia improves myocardial tolerance to ischemia by activating nitric oxide synthase (NOS) and mitochondrial ATP-sensitive K ϩ (K ATP ) channels (2,6). Moreover, the severity of intervened hypoxia is apparently a required condition for cardioprotection (2,3).…”
Section: Cardiac Hemodynamicsmentioning
confidence: 99%
“…Nonetheless, the administration of this nonselective NOS inhibitor significantly lowered NOx levels in all the experimental groups. Because it is well known that L-NAME is a NOS inhibitor (Viñ as et al, 2006;Bertuglia, 2008), the decrease reported here in NOx levels and in situ NOS activity should be attributed to the inhibition of NOS isoforms.…”
Section: Discussionmentioning
confidence: 60%
“…In this sense, while some authors showed that inhibition of NO synthesis by L-NAME decreased greatly the production of lung TBARS after ischemia/reperfusion (Ischiropoulos et al, 1995), others found that the same NOS inhibitor increased the concentrations of TBARS after intermittent hypoxia in hamster cheek pouch microcirculation (Bertuglia, 2008). Regarding apoptosis, Maejima et al (2003) reported that L-NAME greatly increased the apoptosis rate in neonatal rat cardiomyocytes under ischemia/reperfusion, indicating that the NO released during these situations exerts an antiapoptotic effect.…”
Section: Discussionmentioning
confidence: 99%